Homozygous mutations in C1QBP as cause of progressive external ophthalmoplegia (PEO) and mitochondrial myopathy with multiple mtDNA deletions. Issue 10 (22nd July 2020) - Marchet, Silvia; Legati, Andrea; Nasca, Alessia; Di Meo, Ivano; Spagnolo, Manuela; Zanetti, Nadia; Lamantea, Eleonora; Catania, Alessia; Lamperti, Costanza; Ghezzi, Daniele
Abstract: Biallelic mutations in the C1QBP gene have been associated with mitochondrial cardiomyopathy and combined respiratory‐chain deficiencies, with variable onset (including intrauterine or neonatal forms), phenotypes, and severity. We studied two unrelated adult patients from consanguineous families, presenting with progressive external ophthalmoplegia (PEO), mitochondrial myopathy, and without any heart involvement. Muscle biopsies from both patients showed typical mitochondrial alterations and the presence of multiple mitochondrial DNA deletions, whereas biochemical defects of the respiratory chain were present only in one subject. Using next‐generation sequencing approaches, we identified homozygous mutations in C1QBP . Immunoblot analyses in patients' muscle samples revealed a strong reduction in the amount of the C1QBP protein and varied impairment of respiratory chain complexes, correlating with disease severity. Despite the original study indicated C1QBP mutations as causative for mitochondrial cardiomyopathy, our data indicate that mutations in C1QBP have to be considered in subjects with PEO phenotype or primary mitochondrial myopathy and without cardiomyopathy. Abstract : We identified homozygous mutations in C1QBP in two unrelated adult patients presenting with progressive external ophthalmoplegia (PEO) and mitochondrial myopathy. Patients' muscle showed multiple mitochondrial DNA deletions and a strong reduction in the amount of the C1QBP protein. Despite the original study indicated C1QBP mutations as causative for mitochondrial cardiomyopathy, our data indicate that C1QBP mutations have to be considered in subjects with PEO phenotype or primary mitochondrial myopathy and without cardiomyopathy.